Towards a history of secularization and secularism in Argentina (Quinto Sol, 2011)
Discussing with the frame on the same phenomena recently proposed by Fortunato Mallimaci, this paper suggests a periodization and some hypotheses for the interpretation of secularism and secularization process in Argentina from the Bourbon reforms to the present. From an explanation of the sense that the author gives to the concepts of secularism and secularization, it offers a periodization scheme that appeals to the concepts of “umbral de secularización” and “pacto laico” coined by Jean Baubérot for France and for Latin Europe. As an interpretive scheme, the article does not constitute a summary of the history of Catholicism or the relations between Church and State. For this reason, the stages that the author considers are worth reinterpreting -essentially the turn of the century-have deserved more attention than others and therefore have greater development.
Keywords: religion; secularization; secularity